Moving images in relating to the Bible to modern Filipino children to promote Bible reading - Bernardino, Jeremy I. (2013)
A relatively low habit of reading the Bible compare to how children value the importance of the Bible. Because of the serious characteristic that children perceived, it can serve as a hindrance for children to learn and understand the Bible. Moving Images would be a great tool in igniting the interest of children towards the Bible. This paper then explores in combining live action scenes and animation in relating the Bible to urban Filipino children. Seeing the relevance of the Bible to modern life will help children easily grasp the message and apply the teachings to daily life. Ang Mahiwagang Libro, a television series about a magical book that imparts valuable lessons to children. The magical book represents the Bible, which serves as the bridge that connects the past in guiding the present people. Bible characters will immerse in modern Filipino urbanized society to help build up morals and amplify Bible learning to Filipino children.
"April 2013."
Thesis (BFA)--University of the Philippines, Diliman.
Keywords: Motion pictures; Bible -- Children's use -- Philippines; Bible -- Appreciation -- Philippines